Foreign body of fractured tracheal cannula in the bronchus after tracheostomy - Handoko, Cavin; Murdiyo, Mohammad Dwijo (PERHATI-KL, 2023)
Background: Foreign body of fractured tracheal cannula in tracheobronchial tract is one of rarecomplication of tracheostomy. Symptoms appear in the form of respiratory distress and if not properlytreated may threaten patient’s life. Objective: To know the causative factors, management, and preventionof tracheal cannula foreign body in tracheobronchial tract. Case report: A 3-year-old boy reported with a foreign body of fractured tracheal cannula in his bronchus after tracheostomy. Method: Review of evidence-based literatures with keywords ”foreign body” AND ”tracheal cannula” on Google Scholar. Result: Extraction of foreign body of fractured tracheal cannula was performed by rigid bronchoscopy via the stoma, under general anesthesia, in all of the case reports in the literatures. After the procedure, the respiratory distress improved and patients could be discharged from the hospital. Conclusion: The definitive management of foreign body of fractured tracheal cannula in tracheobronchial tract by using rigid bronchoscopy transtracheostomy under general anesthesia is effective. Education and knowledge about post-tracheostomy care and follow up, are the keys to prevent such incidents. Keywords: foreign body, tracheal cannula, bronchoscopy